Seismic Shot Point Navigation Data from the Greenland Margin acquired during R/V Maurice Ewing expedition EW9607 (1996) (IEDA: Marine-Geo Digital Library, 2010)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Maurice Ewing expedition EW9607 conducted in 1996 (Chief Scientist: Dr. W. Steven Holbrook). These data files are of ASCII format and include Seismic Shot Point Navigation data that provide the primary seismic navigation source for this cruise. Data were acquired as part of the projects: Seismic Investigation of the Greenland Margin (SIGMA) and Deep Structure of a Hotspot Influenced Rifted Volcanic Margin: A Joint U.S.-Danish Seismic Experiment off SE Greenland, and funding was provided by NSF grant: OCE94-16631.